SLPI facilitates cell migration by regulating lamellipodia/ruffles and desmosomes, in which Galectin4 plays an important role. Issue 1 (1st January 2020) - Mizutani, Yusuke; Omagari, Daisuke; Hayatsu, Manabu; Nameta, Masaaki; Komiyama, Kazuo; Mikami, Yoshikazu; Ushiki, Tatsuo
ABSTRACT: To elucidate the underlying mechanism of secretory leukocyte protease inhibitor (SLPI)-induced cell migration, we compared SLPI-deleted human gingival carcinoma Ca9-22 (ΔSLPI) cells and original (wild-type: wt) Ca9-22 cells using several microscopic imaging methods and gene expression analysis. Our results indicated reduced migration of ΔSLPI cells compared to wtCa9-22 cells. The lamellipodia/dorsal ruffles were smaller and moved slower in ΔSLPI cells compared to wtCa9-22 cells. Furthermore, well-developed intermediate filament bundles were observed at the desmosome junction of ΔSLPI cells. In addition, Galectin4 was strongly expressed in ΔSLPI cells, and its forced expression suppressed migration of wtCa9-22 cells. Taken together, SLPI facilitates cell migration by regulating lamellipodia/ruffles and desmosomes, in which Galectin4 plays an important role.